(untitled) (REVISTA SAYWA, 2023)
In this issue of Saywa Magazine, recognition is given to women working in Sciences, from the Opinion and UAN Characters sections. It also addresses some testimonials about SARS-CoV-2/Covid-19 that were sent to the magazine at the time.